Funtional Properties of Starch Yam (Dioscorea bulbífera,Dioscorea trífida y Dioscorea esculenta) - Espitia, Javier; Salcedo, Jairo; Garcia, Carlos (Rev. Téc. Fac. Ing. Univ. Zulia, 2016)
The physicochemical and rheological properties of three yam (D.bulbifera, D.trifida and D.esculenta) species were studied using a completely random with unifactorial arrangement design. The results presented significant differences (p < 0,05) with a water absorption capacity between 134% and 165%, electrical capacity between 100,7 Î¼ohms cm-1 and Solubilities values at 30°C, 50°C and 70°C of 15,1% to 13,8, 13,9 to 15,5% and 14,0 to 15,4% respectively. The amylose content showed values between 2,9% and 19,32%, gelatinization temperature between 79°C and 79,9°C, pH values between 6,1 to 7,8. Overall species of yam exhibited pseudoplastic behavior. The functional properties of native of yam starch D.trifida and D.esculenta species be showed attractions for use as stabilisers to freezing and thawing, starch of the species D.trifida especies cam be applied to barkery products deb its greater water capacity retention, maximum viscosity at 90°C (543U.B.) and low resistance to the syneresis. The properties exhibited by the native starches provide alternatives to increase its resistance to stressful treatments using physicochemical changes.